2006
DOI: 10.1002/sim.2550
|View full text |Cite
|
Sign up to set email alerts
|

A natural history model of stage progression applied to breast cancer

Abstract: Invasive breast cancer is commonly staged as local, regional or distant disease. We present a stochastic model of the natural history of invasive breast cancer that quantifies (1) the relative rate that the disease transitions from the local, regional to distant stages, (2) the tumour volume at the stage transitions and (3) the impact of symptom-prompted detection on the tumour size and stage of invasive breast cancer in a population not screened by mammography. By symptom-prompted detection, we refer to tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(106 citation statements)
references
References 11 publications
1
105
0
Order By: Relevance
“…The simulations used in this study were based on a previously published tumour growth model which has been shown to fit observed distributions of tumour size at diagnosis reasonably well [28,29]. One of the main assumptions of the model is that tumours grow exponentially until detection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulations used in this study were based on a previously published tumour growth model which has been shown to fit observed distributions of tumour size at diagnosis reasonably well [28,29]. One of the main assumptions of the model is that tumours grow exponentially until detection.…”
Section: Discussionmentioning
confidence: 99%
“…al. [28] and by Abrahamsson and Humphreys [29]. To choose values of the parameters, τ 1 , τ 2 and η, we used data on the tumour size distribution for breast cancers diagnosed during the years 1977-1979 from the Stockholm-Gotland regional quality register.…”
Section: Tumour Growth and Clinical Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…From data on patients who were detected in advanced stage, one can infer that the size at transition must be smaller than the size at detection. The majority of models that aim to infer primary tumor size at stage transition have been applied to breast cancer [11,12,[17][18][19][20][21][22][23][24], but we have found that they can not be directly applied to lung cancer. When modeling the natural history of breast cancer, a common assumption made is that disease stage does not impact the detection of the disease due to clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies of colorectal and lung cancer have described natural history as a series of transformations from normal to mutated epithelium, to malignant clone, to adenoma (Moolgavkar and Knudson, 1981;Luebeck and Moolgavkar, 2002). Studies of lung and breast cancer have described natural history in terms of tumor size and metastatic status, with the risk of metastasis increasing as tumor size increases (Kimmel and Flehinger,1991;Plevritis et al, 2004). Other models in cancer and HIV have taken the concept of natural history to a higher level of abstraction, specifying only that disease progresses from a preclinical or latent state to a clinically apparent or symptomatic state (Louis, Albert and Heghinian, 1978;Walter and Day, 1983;De Gruttola and Lagakos, 1989).…”
Section: Introductionmentioning
confidence: 99%